(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2023)
The public library reflects on the extent of its social function as a cultural equipment conducive to the appropriation of information and, therefore, it should have its actions linked to society. In this scenario, the present research addresses fundamental presentations of concepts and historical aspects about the origins of the public library, bringing its relationship with the Information Science and Librarianship itself. And also conceptions related to the existing municipal public libraries in the state of Alagoas, showing different conditions for them to perform their institutional operation. As methodology it uses descriptive research from data extracted in procedures performed by field survey, but it is also outlined as bibliographic research for theoretical grounds structured in literature review. Therefore, a qualitative- quantitative approach was chosen. Data collection took place by means of variables considered pertinent in the predominant understanding of the literature selected as a theoretical repertoire, and, for the field survey, an analysis will be made from specific resources, namely: e-mails, websites, digital networks, among others. Therefore, this study is not intended to exhaust the discussions, but to stimulate the interest of future research on the theme.